ANALISIS NILAI-NILAI KEARIFAN LOKAL PADA PENGELOLAAN KEUANGAN IURAN WAJIB UPACARA KEMATIAN (PATUS) (Studi Kasus di Desa Adat Penida Kaja) - Ni Wayan Tirta Wahyuni; Anantawikrama Tungga Atmadja (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This research was held at Penida Kaja traditional village, Tembuku village, Tembuku district, Bangli regency. This research uses qualitative method. The data that used in this research are primary data and secondary data. The primary data were collected from interview, observation and documentation. Analytical methods and techniques that used in this research are data collection, data reduction, data presentation, data analysis and drawing conclusions. The result of research states (1) The financial management of indigenous villages Penida Kaja consists of (a) Planning and Budgeting, (b) Implementation, and (c) Reporting and Accountability (2) The values of local wisdom underlie the program still going on without any problems is there is value of team work in local wisdom (menyamabraya) which is become the basic of villagers of Penida Kaja faithfully pay the mandatory dues of the death ceremony (Patus) other than that the money managing Prajuru Adat and the villagers have a based with the value of local wisdom segilikselulukselunglungsebayantaka, paras parossarpanaya which is has meaning of   light is the same as being carried, heavy is the same as being carried out with no strings attached.